2016
DOI: 10.1038/srep27727
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent photoluminescence of surface-engineered silicon nanocrystals

Abstract: In this work we report on temperature-dependent photoluminescence measurements (15–300 K), which have allowed probing radiative transitions and understanding of the appearance of various transitions. We further demonstrate that transitions associated with oxide in SiNCs show characteristic vibronic peaks that vary with surface characteristics. In particular we study differences and similarities between silicon nanocrystals (SiNCs) derived from porous silicon and SiNCs that were surface-treated using a radio-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Herein, the PL emission peak I of the porous SiC can be attributed to the oxygen vacancy in the porous structures. The existence of oxygen vacancies, emitting in the blue light range of 410–470 nm, is a common phenomenon in semiconductor materials 28 , 35 37 . It has been reported that the luminescence peaks at 460 nm (2.7 eV) was derived from the triplet-to-ground transition of a neutral oxygen vacancy defect (O 3 ≡Si-Si≡O 3 ) 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Herein, the PL emission peak I of the porous SiC can be attributed to the oxygen vacancy in the porous structures. The existence of oxygen vacancies, emitting in the blue light range of 410–470 nm, is a common phenomenon in semiconductor materials 28 , 35 37 . It has been reported that the luminescence peaks at 460 nm (2.7 eV) was derived from the triplet-to-ground transition of a neutral oxygen vacancy defect (O 3 ≡Si-Si≡O 3 ) 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the PL properties should depend on the extent of surface oxidation of ncSi-H. Some previous studies have examined the PL emission with different surface configurations [20,21]. Bürkle et al studied theoretically and experimentally hydroxyl (OH) functionalized Si quantum dots (QDs) with different levels of oxidation [22].…”
Section: Introductionmentioning
confidence: 99%
“…There is great interest in integrating opto-electronic and micro-photonic functionalities into the silicon-based platform, which has faced challenges due to the indirect bandgap nature of the silicon. For this reason allotropes of silicon and nanostructured Si have been widely investigated during the last few years as it offer an enhancement in the optical properties compared to bulk Si [1][2][3][4][5][6][7][8][9][10][11] and a pathway to obtain a direct band gap. Due to the enhancement in optical properties, nanostructured Si containing embedded Si nanocrystals is finding important new applications in nano-electronic and photonic devices including transistors, memories, and silicon based light emitting structures for optoelectronics and displays units etc [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the enhancement in optical properties, nanostructured Si containing embedded Si nanocrystals is finding important new applications in nano-electronic and photonic devices including transistors, memories, and silicon based light emitting structures for optoelectronics and displays units etc [12][13][14][15]. The modification of c-Si structure environment is expected to induce a more efficient luminescence than is found in indirect gap bulk c-Si, and also shift the emission from 1.1 eV into the desired visible region [6,16,17], a key goal in opto-electronics. Si nanocrystals offer a viable pathway for fabrication of direct band gap materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation